Chimonocalamus auriculatus, one more new temperate woody bamboo species of the genus (Poaceae: Bambusoideae: Arundinarieae) described from Thailand - Sungkaew, Sarawood; Hodkinson, Trevor R.; Xia, Nianhe; Teerawatananon, Atchara (Phytotaxa, 2018)
Chimonocalamus auriculatus, a temperate woody bamboo (Arundinarieae), from the border between Thailand and Lao PDR, is described and illustrated here. In its vegetative state, the new species can be distinguished from all the other Chimonocalamus species by its conspicuous auricles and oral setae (bristles) on the culm leaf sheath.